European immigrations : trends, structures and policy implications - Okólski, Marek, (IMISCOE research., 2012)
This volume of the latest research in European migration embraces a continent-wide outlook on migration processes and accounts particularly from Southern and Eastern European perspectives. This is accomplished by analyzing the long-term transition that countries undergo from net emigration to net immigration, as well as developments in their migrant inflows, integration, and policy. The mix of authors' representing several academic centers across Europe yet pursuing a common vision of European migration past, present, and future' utilize new empirical evidence, specially designed and collected.'